Development of Natural Tourism Objects as Regional Tourism Destinations in Pesawaran Regency - Agus - Purnomo; Ida - Farida; Arnes - Arnes; Yuli - Vandika (Politeknik Negeri Semarang, 2020)
Pesawaran is one of the Districts of the Lampung Province that has a natural tourism potential is very rich. The existence that is constantly evolving, making the Island of Tegal Mas as the attractions featured in the Pesawaran District. The purpose of this study is to determine the development of the attractions of the Island Tegal Mas seen from the perspective of developers and tourists, the factors that support as well as the impact of the development attractions of the Island Tegal Mas as a tourist destination in the District Pesawaran. This study uses the Theory of Social Practice from Bourdieu. This research uses qualitative research method with case study approach. Source data from interviews with informants and related documents.The sampling technique using purposive sampling.Data collection techniques using observation, interview and documentation.The validity of data using triangulation of sources.Data analysis using interactive model. The results of this study show the development of the attractions of the Island Tegal Mas has improved the quality of management and service of tourism, characterized by an increase in the number of tourist visits Island Tegal Mas. The development of the attractions of the Island Tegal Mas also accompanied by the enthusiastic people of the Village Gebang from the participation as a business selling food in the tourist area, managing parking areas and support facilities to the location of the attractions the Island Tegal Mas with the use of economic capital, social capital and cultural capital. Community participation the Village of Gebang to develop tourism can be seen in the decision that they were fighting for in the area as a tourist area, in practice that can support the activities of the development attractions of the Island Tegal Mas and also in improving the welfare and quality of life of the local community.